Development of Syllable-Based Minibook Media to Train Beginning Reading Skills - Cahyati, Elva; Yuliana, Rina; Rosidin, Odin (LPPM Universitas Primagraha, 2024)
Learning media becomes a tool for teachers to convey information in the form of material to students effectively. However, in reality there are still many teachers who do not use learning media because they use the lecture method which is considered more practical than making media. This research aims to: (1) produce minibook learning media to train initial reading skills, (2) determine the feasibility of learning media minibooks to practice initial reading skills, (3) knowing students' responses to minibook learning media. Development of minibook learning media based on the syllabic method to train beginning reading skills using research and development (R and D) methods. The development stages used in this research use the Brogg and Gall development procedure, which includes: (1) potential and problems (2) data collection, (3) product design,(4) design validation, (5) design revision, (6) test try. The results of this development research are minibook media based on the syllabic method for practicing initial reading skills which have been tested for their suitability by media experts, material experts and language experts. Overall test results show good results, namely obtaining a very decent category with details of material expert 1 giving a score of 75.0%, material expert 2 of 95.0%, language expert of 84.0%, media expert 1 of 88.8 %, and media expert 2 was 82.2%. The score obtained was in the very decent category. Based on the results of the media feasibility trial, it can be concluded that the minibook learning media based on the syllabic method for practicing initial reading skills is very suitable for use at SDN Rancaranji, especially in the lower classes.